Bioactivities of Purple Shamrock (Oxalis Triangularis) Crude Extract and Evaluation of Shamrock Topical Antibacterial Gel - Dupra, Krizelle Joy; Aceret, Robert (International Journal of Integrated Science and Technology, 2024)
This study delves into the intricate dynamics of the skin microbiome, focusing on its susceptibility to infection when the skin's protective barrier is compromised. Through a comprehensive examination of wound infections, the research underscores the prevalence of acute wounds and their profound impact on morbidity and mortality rates, particularly in developing nations like the Philippines. Despite adherence to WHO protocols, surgical site infections (SSI) remain alarmingly high, necessitating innovative interventions. Enter topical antibacterial agents, offering targeted therapy with minimal systemic impact. Leveraging the medicinal properties of O. triangularis, the study formulates and evaluates a topical antibacterial gel, unveiling its remarkable efficacy in wound healing and bacterial inhibition. Findings reveal promising results, exhibiting accelerated healing and notable antibacterial activity against E. coli. Moreover, its stability and non-irritant nature further accentuate its potential as a cost-effective solution for wound management. This research heralds a promising paradigm shift in wound care, advocating for the integration of botanical extracts in topical formulations for enhanced therapeutic outcomes.